Other Diagnostic Tests for Young-Onset Type 2 Diabetes Mellitus - Huamán Chavarry, Katty Elizabeth; Pacco Valdivia, Jorge Luis; Salvador-Carrillo, Andrea Elvira (Journal of the ASEAN Federation of Endocrine Societies, 2024)
We have read with interest the article entitled “A Cross-sectional Study to Evaluate Beta Cell Function in Individuals with Newly Diagnosed Young-Onset Type 2 Diabetes Mellitus and its Complications,”1 elevated C-peptide levels are indicative of both insulin resistance and beta cell malfunction. These factors are directly linked to the development of complications associated with young-onset Type 2 Diabetes Mellitus (YO-T2DM), including obesity, hypertension, and diabetic kidney disease. The present letter aims to expand the current diagnostic testing options for early detection of YO-T2DM.